Manajemen Risiko Fiskal dalam Kebijakan Subsidi LPG 3 Kg: Studi Kasus di Provinsi Jawa Barat - Riki Satia Muharam; Rusli, Budiman; Karlina, Nina; Candradewini, Candradewini (MAMEN: Jurnal Manajemen, 2025)
The 3-kilogram LPG subsidy is one of Indonesia’s key fiscal policy instruments aimed at protecting the purchasing power of low-income households and micro-enterprises. However, its implementation—particularly in West Java Province—faces significant challenges, including targeting inaccuracies, budget overruns, and increasing fiscal dependency on the central government. This study aims to analyze the forms of fiscal risks arising from the 3-kg LPG subsidy policy and identify relevant fiscal risk management strategies at the regional level. Employing a qualitative descriptive approach and a case study of West Java, the findings reveal various fiscal risks such as inefficient spending, budget diversion from productive sectors, and regional budget instability. To address these challenges, the study recommends implementing targeted subsidies based on integrated socioeconomic data, strengthening digital verification systems, diversifying alternative energy sources, and enhancing fiscal transparency and local government capacity. These findings highlight the urgent need for energy subsidy reform that is more equitable, efficient, and sustainable, while preserving regional fiscal resilience amid dynamic economic pressures.